2008
DOI: 10.1177/152692480801800109
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of Psychosocial Factors in the Evaluation of Living Donors

Abstract: Results of donor outcome studies indicate that most living donors report a positive psychosocial response to donation. However, negative psychosocial outcomes have also been reported. Evaluation guidelines have been proposed, although a standardized evaluation specific to living donors is not yet available. In an effort to determine what psychosocial factors should be considered in a comprehensive evaluation of living donors, an extensive literature review was undertaken that was focused on previously proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 51 publications
(155 reference statements)
0
20
0
Order By: Relevance
“…Perceptions of inadequate understanding have, however, been linked to deteriorating social relationships, including separations and divorce in the aftermath of donation (38,39). A recent review suggested that postdonation feelings of being inadequately informed were also associated with HRQOL generally, and with psychological well-being in particular (40). Given work in other patient populations suggesting that inadequate understanding about a medical procedure is linked to greater anxiety about undergoing the procedure and more somatic symptoms in its aftermath (4143), living donors with lower levels of understanding may be at risk for heightened anxiety predonation, and they may have more worry about complications and long-term health effects postdonation.…”
Section: Evidence To Date On Psychosocial Outcomesmentioning
confidence: 99%
“…Perceptions of inadequate understanding have, however, been linked to deteriorating social relationships, including separations and divorce in the aftermath of donation (38,39). A recent review suggested that postdonation feelings of being inadequately informed were also associated with HRQOL generally, and with psychological well-being in particular (40). Given work in other patient populations suggesting that inadequate understanding about a medical procedure is linked to greater anxiety about undergoing the procedure and more somatic symptoms in its aftermath (4143), living donors with lower levels of understanding may be at risk for heightened anxiety predonation, and they may have more worry about complications and long-term health effects postdonation.…”
Section: Evidence To Date On Psychosocial Outcomesmentioning
confidence: 99%
“…Currently, the conceptualization of optimal psychosocial health in LKDs includes perceived benefits of donation, decision stability, healthy donor-recipient relationship, and limited financial impact (Dew & Jacobs, 2012). Collectively, study findings and broader conceptualization of donor outcomes have led to improvements in informed consent (Parekh et al, 2008; Thiessen, Kim, Formica, Bia, & Kulkarni, 2013) and psychosocial evaluation (Dew et al, 2007; Schroder, McDonald, Etringer, & Snyders, 2008) processes for potential LKDs, as well as the inclusion of two psychosocial outcomes (donor work status, loss of insurance due to donation) as part of the UNOS-mandated LKD follow-up requirements.…”
Section: Introductionmentioning
confidence: 99%
“…These residual feelings must be distinguished from what, in contrast, can be termed acute ambivalence, i.e., feelings of indecision so marked that it is determined in the psychosocial evaluation that the prospective donor is unable to give adequate informed consent to proceed. 7,10,11,95 Residual ambivalence, instead, pertains to feelings that remain shortly before donation, despite the fact that the donor intends to proceed with donation. While acute ambivalence, resulting in a rule-out of the individual as a donor, is uncommon (<2% of rule-outs), 9699 some degree of residual ambivalence before donation has been noted in up to 75% of donors.…”
Section: Introductionmentioning
confidence: 99%